FINANCIAL BARRIERS AND ACCESSIBILITY OF HEALTH SERVICES AMONG PATIENTS WITH NON-COMMUNICABLE DISEASES IN URBAN AND RURAL AREAS IN THE PELAGONIAN REGION - Popovska Kljuseva, Svetlana; Velikj Stefanovska, Vesna; Kochinski, Dragan (Journal of Morphological Sciences; Vol 6 No 3 (2023): JMS, 2023)
Financial barriers and accessibility of health services for patients with non-communicable diseases is a topic and issue of health policy, considering the impact of the world crisis on the provision of health care and the increased vulnerability of patients with non-communicable diseases.  The aim of this study is perceive the possible differences in financial barriers and accessibility of health services according to the place of residence in an urban or rural area of patients with non- communicable diseases.  This is a cross-sectional analytical study, conducted in the period June-September 2023. Patients from the Pelagonian region with at least one chronic disease (heart attack, stroke, cancer, COPD, asthma, diabetes) were included. A survey questionnaire was used for completing the purposes of the study. A total of 118 patients were included in the study. In the last 12 months, 13 (26.5%) of the urban respondents and 21 (31.3%) of the rural respondents postponed a health examination due to the cost. Patients living in rural areas face insufficient access to pharmacies 4.39 times more compared to those from urban areas,  general practitioners are 3.08 times more unavailable, and also the patients face with a problem of getting a examination by specialist 5.76 times more often compared to those living in urban areas. Patients with non-communicable disease living in rural areas face additional challenges in terms of access to health care and services. The results of this study make an important contribution to emphasize the importance of the place of residence for achieving health equity. Keywords: access, financial barriers, health services, health care, non-communicable diseases.